2021
DOI: 10.13057/biodiv/d221029
|View full text |Cite
|
Sign up to set email alerts
|

Species identification and prevalence of gastrointestinal helminths in Indonesian native chickens, and its impact on egg production

Abstract: Abstract. Zalizar L, Winaya A, Malik A, Widodo W, Suyatno, Anggraini AD. 2021. Species identification and prevalence of gastrointestinal helminths in Indonesian native chickens, and its impact on egg production. Biodiversitas 22: 4363-4369. Gastrointestinal parasite (GIP) infection is a severe problem of local chicken production, such as poultry and egg. Hence, the proper strategy to control the parasite invasion should be implemented regarding chicken productivity performance. Moreover, the existing environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…Normal chicken hematocrit values are 22-35%, with an average of 30%. Furthermore, (Zalizar et al, 2023) reported that the average number of native chicken erythrocytes ranged from 2.3 -3.5%.…”
Section: Hematocrit Valuementioning
confidence: 99%
“…Normal chicken hematocrit values are 22-35%, with an average of 30%. Furthermore, (Zalizar et al, 2023) reported that the average number of native chicken erythrocytes ranged from 2.3 -3.5%.…”
Section: Hematocrit Valuementioning
confidence: 99%
“…Cacing Raillietina spp. memiliki morfologi ukuran panjang lebih dari 10 cm, rostelum dipersenjatai kait berbentuk palu yang tersusun dalam lingkaran ganda, asetabulanya juga dipersenjatai kait kecil dengan garis bagan melingkar yang tersusun dalam beberapa lingkaran, dan tubuh cacing tersusun oleh proglotidproglotid (Zalizar et al, 2021). Lesi yang terdapat pada anterior jejunum dan caecalcolon sekum disebabkan oleh infestasi cacing di dalam usus ayam.…”
Section: Pemeriksaan Penunjangunclassified